The upper cervical spine tumor pathology c1-c2 - D. Serban; N. A. Calina; Fl. Exergian; M. Podea; C. Zamfir; E. Morosanu; A. Giovani; Gh. Checiu (Romanian Neurosurgery, 2012)
Surgical treatment of upper cervical spine tumors, whether they are vertebral, epidural, subdural or intramedullary, raises technical and decisional difficulties regarding the approach of the region as well as in maintaining its stability. The authors performed a retrospective study on C1, C2 spinal tumor pathology, managed surgically in the Spinal Surgery Department of Bagdasar Arseni Clinical Hospital, between January 2007 and December 2011. We included in the study 44 patients, operated for C1, C2 cervical spine tumors, 23 men and 21 women with ages between 13 and 71 years. The pathology included 24 C1-C2 vertebral tumors, 11 subdural tumors, 2 epidural tumors and 7 intramedullary tumors. Presenting symptoms were cervical pain, occipital neuralgia, medullary compression syndrome, and/or cranio-spinal junction instability. The purpose of surgery was to establish a histopathologic diagnosis and to decompress the neural elements by attempting a total tumor removal as well as to stabilize the cranio - cervical junction in order to improve the patient's quality of life. The approach was chosen based on tumor location, prognosis and the need for fixation. For 6 patients an anterior approach was used, for 31 pacients we used a posterior approach and 7 patients required a combined anterior and posterior approach. Neurological improvement was observed in 17 patients, with a mean increase of 8 points on ASIA scale, 7 patients worsened immediately postoperatively with a mean decrease of 10 points on ASIA scale, (2 patients died), and 20 patients without neurological deficits preoperatively remained unchanged. In all cases where the craniospinal junction instability was the cause of occipito-cervical pain we noted the disappearence of pain after surgery. The development of new surgical techniques and fixation systems paved the way to a successful treatment for these difficult tumors, some of them considered inoperable in the past.